Determination of Chicken Egg Distribution Channels in Bumdes Makmur Rejo Using the Saving Matrix Method - Sulistyorini, Arum; Putri Farahdiansari, Ardana; Pratama, Rio Chandra (Yayasan Gema Bina Nusantara, 2023)
Distribution is very important in a company, because distribution is an activity of moving goods or services from suppliers to customers. Any goods or services can be transported from one company location to a consumer location. The distance between locations can also affect the delivery process. Delivery of goods is a basic need every day that can carry out the delivery process quickly and safely so that the goods are delivered on time so that the company can get more profits. This BUMDesa has problems with the distribution of egg shipments where the distribution is still not effective and efficient. This study uses the saving matrix method to determine the most efficient and effective distance so as to save time and fuel costs. The results of this study The initial route of 65.08 Km costs Rp. 442,544 and the required fuel is 6,508 Lt. Meanwhile, the new route 56.4 will cost Rp. 383,520 and the required fuel is 5.64 Lt.